(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In this article money laws are discovered. A problem of the lack of systematic approach to the laws and to their implementation is pointed out. The author proposes a system of money laws and overviews its functioning, taking into account theories developed by various scientists.